If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10x + 2x + 8x + -7x + 17(x + -1) = 43 Reorder the terms: 10x + 2x + 8x + -7x + 17(-1 + x) = 43 10x + 2x + 8x + -7x + (-1 * 17 + x * 17) = 43 10x + 2x + 8x + -7x + (-17 + 17x) = 43 Reorder the terms: -17 + 10x + 2x + 8x + -7x + 17x = 43 Combine like terms: 10x + 2x = 12x -17 + 12x + 8x + -7x + 17x = 43 Combine like terms: 12x + 8x = 20x -17 + 20x + -7x + 17x = 43 Combine like terms: 20x + -7x = 13x -17 + 13x + 17x = 43 Combine like terms: 13x + 17x = 30x -17 + 30x = 43 Solving -17 + 30x = 43 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '17' to each side of the equation. -17 + 17 + 30x = 43 + 17 Combine like terms: -17 + 17 = 0 0 + 30x = 43 + 17 30x = 43 + 17 Combine like terms: 43 + 17 = 60 30x = 60 Divide each side by '30'. x = 2 Simplifying x = 2
| 8(h-4)-7(h+8)=-80 | | 7n^2-20n-32=0 | | 2x^2+3xy-35y^2= | | 2x^2+19xy+35y^2= | | n^2*n^8= | | -7+5x=-42 | | x^3-18x^2+432= | | s^2-2s-63= | | 10+4a=-6 | | 9x^2+81x=0 | | 2m+1=9 | | 12+6x=-54 | | b^2-13b+40=0 | | x^2+18x-225=0 | | 2x^2-6x-55=0 | | 3+4x=-57 | | x^2+18x=225 | | 38=-4(g+3)+7(-2-4g) | | 6(2x-3)+2(6x+2)=2(x+1) | | 3y+3(1-y)-y=10 | | (2x-5)+15=67 | | 6(y-5)=4(4+y) | | -2x^2+5x+33=21 | | b+21/6=-13/8 | | -2x^2+5x+33=0 | | 6(4-5)=4(4+y) | | -5(2b+7)-7(-b-8)=0 | | 4x+5y=19 | | 2x^2-5x-33=21 | | 3y^2+7=2y | | 6y-30=16+4y | | -48=6(-6h-2) |